Modification of the coupled integral equations method for calculation of the accelerating structure characteristics - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2022)
In this paper we present modification of coupled integral equations method (CIEM) for calculating the characteristics of the accelerating structures. In earlier developed CIEM schemes the coupled integral equations are derived for the unknown electrical fields at interfaces that divide the adjacent volumes. In addition to the standard division of the structured waveguide by interfaces between the adjacent cells, we propose to introduce new interfaces in places where electric field has the simplest transverse structure. Moreover, the system of coupled integral equations is formulated for longitudinal electrical fields in contrast to the standard approach where the transverse electrical fields are unknowns. The final vector equations contain expansion coefficients of the longitudinal electric field at these additional interfaces. This modification makes it possible to deal with a physical quantity that plays an important role in the acceleration of particles (a longitudinal electric field), and to obtain approximate equations for the case of a slow change in the waveguide parameters. Представлено модифікацію методу зв’язаних інтегральних рівнянь для розрахунку характеристик прискорювальних структур. У раніше розроблених схемах зв’язані інтегральні рівняння формулюються для невідомих електричних полів на поверхнях розділу, що ділять суміжні об’єми. На додаток до стандартного поділу структурованого хвилеводу на межі розділу між сусідніми комірками пропонуємо ввести нові інтерфейси в місцях, де електричне поле має найпростішу поперечну структуру. Крім того, система зв’язаних інтегральних рівнянь сформульована для поздовжніх електричних полів на відміну від стандартного підходу, де поперечні електричні поля невідомі. Кінцеві векторні рівняння містять коефіцієнти розкладання поздовжнього електричного поля на цих додаткових поверхнях розділу. Ця модифікація дає змогу мати справу з фізичною величиною, яка відіграє важливу роль у прискоренні частинок (поздовжнє електричне поле), та отримати наближені рівняння для випадку повільної зміни параметрів хвилеводу. Представлена модификация метода связанных интегральных уравнений для расчета характеристик ускоряющих структур. В разработанных ранее схемах связанные интегральные уравнения формулируются для неизвестных электрических полей на границах раздела, разделяющих соседние объемы. В дополнение к стандартному разделению структурированного волновода границами раздела между соседними ячейками предлагается ввести новые границы раздела в местах, где электрическое поле имеет простейшую поперечную структуру. Кроме того, система связанных интегральных уравнений формулируется для продольных электрических полей в отличие от стандартного подхода, когда поперечные электрические поля неизвестны. Окончательные векторные уравнения содержат коэффициенты разложения продольного электрического поля на этих дополнительных границах раздела. Эта модификация позволяет оперировать с физической величиной, играющей важную роль в ускорении частиц (продольным электрическим полем), и получить приближенные уравнения для случая медленного изменения параметров волновода.